Photochemically Controlled Molecular Machines with Sequential Logic Operation - Avellini, Tommaso; Baroncini, Massimo; Ragazzon, Giulio; Silvi, Serena; Venturi, Margherita; Credi, Alberto (Israel journal of chemistry, 2014)
A molecular machine is an assembly of molecular components (i.e., a supramolecular structure) designed to perform specific mechanical movements in response to external stimuli. Biomolecular machines are essential for living organisms and are proven examples of the feasibility and utility of nanotechnology. Artificial molecular machines have been built in the laboratory and their use for smart materials and devices is the subject of much investigation. Here we discuss molecular machines based on rotaxane‐like species, whose operation depends both on the type and sequencing of stimuli. These systems have the potential to store information and when carefully designed, the interplay of thermodynamic and kinetic features of supramolecular assemblies can yield sequential behavior. The investigation of ‘intelligent’ molecules capable of recognizing a specific input code can introduce new concepts to the field of chemistry and stimulate research in the bottom‐up construction of nanodevices.